IMPLEMENTASI KEBIJAKAN PENANGGULANGAN KEMISKINAN DI KOTA MALANG - SARI, YULI INDAH; Tri Hardianto, Willy; Purwatiningsih, Annisa; Widi Lestari, Asih (Universitas 17 Agustus 1945 Surabaya, 2023)
The definition of poverty can be broadly divided into two, namely absolute poverty and relative poverty. Absolute poverty is a condition where a person's income level is not sufficient to meet their basic needs. Policy is a series of concepts and principles that serve as guidelines and the basis for plans in carrying out work, leadership and ways of acting. The term can be applied to governments, private sector organizations and groups, as well as individuals. Policies are different from regulations and laws. If the law can impose or prohibit a behavior (for example a law that requires the payment of income tax), policy only guides actions that are most likely to obtain the desired results, the implementation of public policy as a form of thought process and human action that is well planned, rational, efficient and effective as an effort to create order and order in various state or government tasks in order to create shared prosperity based on justice and equality. The aim of this research is to determine the implementation of poverty alleviation in Malang City, to find out the supporting and inhibiting factors for the implementation of poverty alleviation in Malang City. This research uses qualitative methods by collecting data through observation, interviews and documentation using snowball sampling to determine informants. Data analysis was carried out through the stages of data collection, data presentation and drawing conclusions. From this research, the results showed that the implementation of the poverty alleviation policy in the city of Malang has gone well and according to procedures, and monitoring and outreach to the community has also been carried out, however there are several obstacles in the effort to receive this aid, namely the data provided by the Ministry of Social Affairs still takes time. which is old. Key words: poverty, overcoming, Malang City.